Revisiting the fundamentals of p-nitrophenol analysis for its application in the quantification of lipases activity. A graphical update. - Syedd-León, Randall (2020)
p-Nitrophenol (pNP) is a widely used compound for analytical determinations of several esterases (EC. 3.1.1.X), including lipases (E.C. 3.1.1.3). Most enzymatic measurements employ pNP derivatives such as esters, which are broken down by enzymatic hydrolysis, releasing pNP that is quantified by its absorbance at 410 nm. Although this type of methods was developed a few decades ago, the spectrophotometric analysis of pNP requires analytical measurements of pH and temperature to achieve reliable determinations. The aim of this paper is to offer a graphical update of how pH and temperature affect the p-nitrophenol absorbance at different wavelengths in lipase emulsified media, due to its relevance for the quantitative determination of lipase activity using spectrophotometric methods. To highlight the importance of each variable involved in this analysis, we dissolved pNP in emulsified media (for lipase activity quantification) at several pH values from 4.00 to 11.00, and measured its absorbance in a range of 270 nm – 500 nm and at several temperatures from 25°C to 50°C. The absorption patterns of pNP under the established conditions were graphed in 3D plots. The constructed 3D plots showed that, regardless of the temperature, below pH 6.00, pNP predominantly absorbs at 317 nm, due to the greater abundance of its protonated form, which is completely predominant at pH 3.50 and below. On the other hand, at pH 10.0 and above, the major absorption occurs at about 401 nm, confirming that the equilibrium is completely shifted to the pNP anionic form. These results also indicate that close to neutral pH value pNP, it displays a temperature dependence effect, increasing absorbance to 410 nm at higher temperatures. Due to many analytical determinations of enzymatic activities, the release of pNP is carried around pH 7.00. It is necessary to consider the determinant role of both pH and temperature over these measurements, how these variables must be strictly controlled, and how the calibration curves and blanks should take the reaction media pH and temperature into account.